1991
DOI: 10.1038/353326a0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of self peptides bound to purified HLA-B27

Abstract: A pool of endogenous peptides bound to the human class I MHC molecule, HLA-B27, has been isolated. Microsequence analysis of the pool and of 11 HPLC-purified peptides provides information on the binding specificity of the HLA-B27 molecule. The peptides all seem to be nonamers, seven of which match to protein sequences in a database search. These self peptides derive from abundant cytosolic or nuclear proteins, such as histone, ribosomal proteins, and members of the 90K heat-shock protein family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
416
3
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(439 citation statements)
references
References 44 publications
19
416
3
1
Order By: Relevance
“…Since peptide-elution studies have shown the HLA-B*2705 B-pocket binds almost exclusively arginine [12,28], variable viruses may thus readily escape immune recognition by any alteration of P2. Interestingly two subtly different mechanisms of binding the P2R have been observed in different crystal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since peptide-elution studies have shown the HLA-B*2705 B-pocket binds almost exclusively arginine [12,28], variable viruses may thus readily escape immune recognition by any alteration of P2. Interestingly two subtly different mechanisms of binding the P2R have been observed in different crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous crystallographic and peptide-elution studies of HLA-B*2705 derived from tissue culture have demonstrated that HLA-B*2705 almost invariably binds self peptides with an arginine at peptide position 2, this side chain being accommodated in the B-pocket [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We first looked for evidence of extended versions of peptides identified in either ERAP1-silenced cells or ERAP1-competent cells. As shown in Table 1 (28,(32)(33)(34).…”
Section: Erap1 In Hla-b27 Peptide Presentation 287mentioning
confidence: 99%
“…Several theories have been proposed, including molecular mimicry and involvement of genes closely linked to the HLA-B locus (1). However, none of these, nor the identification of self peptides bound to purified HLA-B27 molecules, has shed any decisive light on the question (2). If HLA-B27 functions as an immune response gene in the pathogenesis of spondylatihropathies, the effect should be apparent in the immune response.…”
Section: Bacterial Antibodies In Hla-b27+ Healthy Individualsmentioning
confidence: 99%